Strategi Pemasaran Dalam Peningkatan Daya Saing UMKM Pada Toko Pkk Desa Simpang Tiga Kec. Sawit Seberang Kab. Langkat - Utami, Nyda; Sari, Maya (Jurnal Ekonomi dan Keuangan Syariah, 2022)
Abstract: Competition in the business world cannot be separated from the development of the environment faced. The business environment that has a big influence on marketing success is the development and advancement of technology, as well as changes in people's lifestyles. In an effort to achieve the success of marketing their products, an entrepreneur or marketer must be able to formulate a marketing strategy decision to be used. This research was conducted in a trading business owned by PKK, Simpang Tiga Village, Palm Subdistrict across Langkat Regency. The purpose of this study was to determine the marketing strategy carried out by the trading business belonging to the PKK Simpang Tiga Village, Sawit Seberang District, Langkat Regency to increase the competitiveness of MSMEs and to find out the obstacles faced by the trading business belonging to the PKK Simpang Tiga Village, Sawit Seberang District, Langkat Regency in running a business. This study uses the interview method. This type of research is descriptive qualitative. The results of this study indicate that the marketing strategy carried out by the trading business belonging to PKK Simpang Tiga Village, Sawit Seberang District, Langkat Regency is a marketing mix strategy, which consists of product, price, place and promotion. Obstacles faced by the trading business of PKK Simpang Tiga Village, Sawit Seberang District, Langkat Regency, namely competitors, Covid-19 and public trust. As for efforts to deal with these obstacles, the trading business belonging to the Simpang Tiga Village PKK has made new innovations both in products and promotional methods to attract customers.